Nutrition in diabetes - Osama, Hamdy; Mohd Yusof, Barakatun Nisak (Elsevier, 2016)
Medical nutrition therapy (MNT) is a key component of diabetes management. The importance of balancing macronutrients, reducing carbohydrate load, lowering glycemic index, and implementing an overall healthy dietary pattern are emerging as better approaches for MNT in diabetes. Recent research points to improved glycemic control, reduction in body weight, and improvement in many cardiovascular risk factors when these approaches are provided by registered dietitians or health care providers. This review article discusses the current evidence about the role of sensible nutrition in diabetes management. Specific eating plans for weight reduction and for patients with type 1 diabetes are also discussed.